Peran Krusial Adab dalam Dunia Pendidikan dan Pembelajaran - Mawar Tsabitah; Siti Masyithoh (STIKes Ibnu Sina Ajibarang, 2025)
The concept of 'adab' (propriety or manners) plays a pivotal role in shaping the moral and ethical foundation of education. This study aims to explore the critical function of adab within educational and instructional contexts. Using a qualitative descriptive approach through literature review, this research reveals that adab contributes not only to discipline and behavior management but also fosters the internalization of values essential for lifelong learning. The integration of adab into the educational process enhances teacher-student relationships and supports character education holistically. It is recommended that educational institutions reconsider their approaches to incorporate adab as a central pillar in curriculum design and daily learning activities.